A Self-Optimizing Mobility Management Scheme Based on Cell ID Information in High Velocity Environment - Dongming Su; Xiangming Wen; Haijun Zhang; Wei Zheng (2010 Second International Conference on Computer and Network Technology, 2010)
Reduction of the operational effort and cost is a key driver for RAN LTE (Long Term Evolution or E-UTRAN). Self-configuring and self-optimizing mechanisms are introduced as a part of Self Organizing Network (SON) to maximize the integrated performance of LTE/LTE-Advanced by improving the efficient of operation and maintenance. Optimization of handover is one of the optimization aspects of Self Organizing Network in LTE-Advanced. High velocity environment, especially multi-service environment usually needs extensively investigation to optimize. Using layer3 filter, hysteresis, and time-to-trigger mechanisms is standardized for LTE Hard handover. In this paper, an interacting self-optimizing handover mechanism based on cell ID information is proposed. We have shown that significant gain can be achieved by the use of optimization mechanism while maintaining low handover rates and ping-pong handover rate.